Intraoperative monitoring during decompression of the spinal cord and spinal nerves using transcranial motor-evoked potentials: The law of twenty percent. Issue 9 (September 2015) - Tanaka, Satoshi; Hirao, Jun; Oka, Hidehiro; Akimoto, Jiro; Takanashi, Junko; Yamada, Junichi
Abstract Motor-evoked potential (MEP) monitoring was performed during 196 consecutive spinal (79 cervical and 117 lumbar) surgeries for the decompression of compressive spinal and spinal nerve diseases. MEP monitoring in spinal surgery has been considered sensitive to predict postoperative neurological recovery. In this series, transcranial stimulation consisted of trains of five pulses at a constant voltage (200–600 V). For the normalization of MEP, we recorded compound muscle action potentials (CMAP) after peripheral nerve stimulation, usually on the median nerve at the wrist 2 seconds before or after each transcranial stimulation of the motor area, for all operations. The sensitivity and specificity of MEP monitoring was 100% and 97.4%, respectively, or 96.9% with or without CMAP compensation (if the threshold of postoperative motor palsy was defined as 20% relative amplitude rate [RAR]). The mean RAR after CMAP normalization, of the most affected muscle in the patient group with excellent postoperative results (recovery rate of a Japan Orthopedic Association score of more than 50%) was significantly higher than that in the other groups (p = 0.0224). All patients with an amplitude increase rate (AIR) with CMAP normalization of more than 20% achieved neurological recovery postoperatively. Our results suggest that if the RAR is more than 20%, postoperative motor palsy can be avoided in spinal surgery. If the AIR with normalization by CMAP after peripheral nerve stimulation is more than 20%, neurological recovery can be expected in spinal surgery.